2020
DOI: 10.1136/jitc-2020-001019
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in immune cell subsets with corticosteroids in patients with solid tumors: implications for COVID-19 management

Abstract: BackgroundThe risk–benefit calculation for corticosteroid administration in the management of COVID-19 is complex and urgently requires data to inform the decision. The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation associated with poor prognosis in both COVID-19 and cancer. Investigating NLR as an inflammatory marker and lymphocyte levels as a critical component of antiviral immunity may inform the dilemma of reducing toxic hyperinflammation while still maintaining effective antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Noteworthy, there is evidence that the use of corticosteroids is associated with a delayed viral clearance in patients COVID-19 ( 40 ). In addition, treatment with glucocorticoids in patients with COVID-19 has been reported to induce an early drop in absolute lymphocyte counts, with prolonged lymphopenia, along with a significant steady increase in the absolute neutrophil count, altogether driving significant increases in the neutrophil-lymphocyte ratio for at least 2 wk ( 41 ). Absolute neutrophil count elevation seen in response to corticosteroid administration is similar to trends associated with increased mortality in several coronavirus studies to include the current SARS-CoV-2 pandemic ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, there is evidence that the use of corticosteroids is associated with a delayed viral clearance in patients COVID-19 ( 40 ). In addition, treatment with glucocorticoids in patients with COVID-19 has been reported to induce an early drop in absolute lymphocyte counts, with prolonged lymphopenia, along with a significant steady increase in the absolute neutrophil count, altogether driving significant increases in the neutrophil-lymphocyte ratio for at least 2 wk ( 41 ). Absolute neutrophil count elevation seen in response to corticosteroid administration is similar to trends associated with increased mortality in several coronavirus studies to include the current SARS-CoV-2 pandemic ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study showed a positive correlation between recent cytotoxic therapy and the mortality rate in COVID-19 patients. It also presented a higher risk in patients who received cytotoxic treatment within two weeks, but if the time was more than three weeks, the risk was lower [ 17 ]. From the results of our study, we can conclude that during cytotoxic treatment, a pandemic patient who can move to alternative treatment should be shifted to safer therapies, and a patient who has no alternative treatment option should continue with cytotoxic treatment with the utmost care and strong protective measures against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…4 A host of studies scrutinizing the use of steroids in viral respiratory diseases showed expected complications of avascular necrosis and diabetes, increased mortality, and secondary infections in influenza and reduced clearance of viral particles in SARS and Middle East respiratory syndrome (MERS) coronavirus outbreaks. 5 Patients plagued with the severe form of COVID-19 disease often find themselves faced with such challenges as coagulopathies and DIC. Infection-induced endothelial dysfunction causes an excess of procoagulant thrombin with concomitant shutting down of the fibrinolytic cascade resulting in a hypercoagulable state which can spur thrombosis by increasing blood viscosity and coupled with hypoxia can activate the hypoxia-induced transcription factor-dependent signaling.…”
Section: Case Presentationmentioning
confidence: 99%
“… 4 A host of studies scrutinizing the use of steroids in viral respiratory diseases showed expected complications of avascular necrosis and diabetes, increased mortality, and secondary infections in influenza and reduced clearance of viral particles in SARS and Middle East respiratory syndrome (MERS) coronavirus outbreaks. 5 …”
Section: Case Presentationmentioning
confidence: 99%